1982
DOI: 10.1037/0097-7403.8.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UCS preexposure on excitatory and inhibitory rabbit eyelid conditioning: An associative effect of conditioned contextual stimuli.

Abstract: Preconditioning experience with the unconditional stimulus (UCS) retards subsequent excitatory conditioning. Three experiments demonstrated that this UCS retardation effect is attenuated by associative manipulations of contextual stimuli of the UCS preexposure environment. The UCS retardation effect was reduced by (a) altering contextual stimuli between preexposure and conditioning (Experiment 1), (b) latently inhibiting contextual stimuli prior to UCS preexposure (Experiment 2), and (c) extinguishing contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 44 publications
10
85
0
Order By: Relevance
“…Hinson found that backward conditioning of the rabbit's eyelid response was more inhibitory if the backward conditioning was preceded by US preexposures. Although Hinson (1982) interpreted his results as being most consistent with the context blocking model, the results are also consistent with both scalar expectancy and opponent-process models. In particular, the use of backward conditioning would be optimal from an opponent-process perspective, since the backward CS occurs near the expected temporal maximum strength of the US's hedonically opposite process.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Hinson found that backward conditioning of the rabbit's eyelid response was more inhibitory if the backward conditioning was preceded by US preexposures. Although Hinson (1982) interpreted his results as being most consistent with the context blocking model, the results are also consistent with both scalar expectancy and opponent-process models. In particular, the use of backward conditioning would be optimal from an opponent-process perspective, since the backward CS occurs near the expected temporal maximum strength of the US's hedonically opposite process.…”
supporting
confidence: 68%
“…In general, models invoke either nonassociative or associative mechanisms (Baker, Mercier, Gabel, & Baker, 1981;Hinson, 1982;Randich & LoLordo, 1979). Nonassociative models emphasize the effects of US preexposure on US-UR reactions, whereas associative models focus on changes in the processing of discrete signals that result when a US is presented alone.…”
mentioning
confidence: 99%
“…Neither our previous research (Saladin & Tait, 1986) nor our subsequent research (Saladin & Tait, 1988) has produced a subject that showed a similar pattern of UR changes. Second, the retardation of the onset of conditioning in Group IO>:20 replicated previous studies that showed that 20 paraorbital shock US preexposures in each of 10 successive sessions produced retardation of excitatory nictitating membrane (Saladin & Tait, 1986) and eyelid (Hinson, 1982) conditioning in the rabbit. Finally, the retardation of conditioning was demonstrated only in the group that showed an increase in mean UR amplitudes during US preexposure.…”
Section: Discussionsupporting
confidence: 72%
“…Methodologically, the control group had the same apparatus exposure as the reacquisition groups had. There is evidence that prior exposure to apparatus cues has a paradoxical effect; specifically, latent inhibition of the apparatus cues facilitates acquisition when pairings of a discrete CS with the US are introduced (Grant & Young, 1971;Hinson, 1982;Maes & Vossen, 1993). Hence, the use of apparatus exposure may set a high baseline, making it more difficult to detect rapid reacquisition but easier to detect retarded reacquisition.…”
Section: Methodsmentioning
confidence: 99%